Implementation Aspects To Secure Criticaldatain Public Cloud Network Using Opnet Simulator (International Journal of Engineering and Computer Science, 2014)
publictoaccesstheseapplication,software and PlatformatlowcostwithoutanySecurityMechanism, but insidethisdeployment Cloudsometimecriticaldatarequired privacyfromglobaluserand   atnowonlyexistingfirewall mechanism usedtoprotectthecriticaldatafromattackers by creatingVirtualprivatenetworkwhichiscostlymechanism forshort period. This paper describes thePublic Cloud Networks,Criticaldata, existingmechanismand proposed Architecturewithimplementationtool